24z^2 + 70z + 49
I'd recommend the FOIL method. FOIL stands for First, Last, Inner, Outer, the pairs of terms that must be multiplied and then summed.
First: 4z*6z = 24z^2
Outer: 4z*7 = 28z
Inner: 7*6z = 42z
Last: 7*7 = 49
Sum: 24z^2 + 28z + 42z + 49 = 24z^2 + 70z + 49
2007-06-07 03:40:33
·
answer #1
·
answered by DavidK93 7
·
0⤊
0⤋
Use the FOIL method (First, Outer, Inner, Last) to multiply each term together:
First terms: 4z * 6z = 24z^2
Outer terms: 4z * 7 = 28z
Inner terms: 7 * 6z = 42z
Last terms: 7 * 7 = 49
Placing these terms together in an equation, we get
24z^2 + 28z + 42z + 49
And combining the like terms, we end up with
24z^2 + 70z + 49
2007-06-07 10:43:35
·
answer #2
·
answered by mattside_bic 2
·
0⤊
0⤋
(4z + 7) (6z + 7) = 24z^2 + 28z + 42z + 49 = 24z^2 + 70z + 49
2007-06-07 10:42:59
·
answer #3
·
answered by Swamy 7
·
0⤊
0⤋
First, we take "4z" and multiply it with "6z", result is 24z^2.
Now, multiply "4z" with "+7", result is 28z.
Now take "+7" and multiply with "6z", result is 42z.
Multiply, "+7" with "+7", result is 49
Now sum it all up: 24z^2 + 70z + 49
2007-06-07 10:49:29
·
answer #4
·
answered by Ankthepot 1
·
0⤊
0⤋
24z^2+70z+49
2007-06-07 10:41:50
·
answer #5
·
answered by MathGuy 6
·
0⤊
0⤋
24z + 49
2007-06-07 11:05:22
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
24z^2+28z+42z+49
24z^2+70z+49
2007-06-07 10:44:03
·
answer #7
·
answered by Raziel Lives 4
·
0⤊
0⤋
24Z^2+28Z+42Z+49
=24Z^2+70Z+49
OK?
2007-06-07 10:45:08
·
answer #8
·
answered by annan 2
·
0⤊
0⤋